Calculation method and predictive analysis of flexural capacity of reinforced concrete beams strengthened with carbon fiber-reinforced polymer sheets applied to the side surfaces - Xiang Liu (PLoS ONE, 2026)
In response to the situation where it is not allowed to stick CFRP cloth at the bottom of a concrete beam and stick it on both sides of the beam, this article analyzes the factors that affect the ultimate flexural bearing capacity of reinforced concrete beams reinforced with CFRP on the side, and provides a calculation method for the flexural bearing capacity of reinforced concrete beams reinforced with CFRP on the side; At the same time, for the convenience of calculation, this paper explores the comprehensive consideration of the tensile force of carbon fiber cloth pasted on the side and the corresponding correction factor η f of the force arm, and analyzes it by fitting a quadratic trend function with the ratio of CFRP pasting height to beam height ( h f / h ). Based on this, the calculation methods for the bending capacity of carbon fiber cloth pasted on the bottom surface according to the “Code” and the bending capacity of carbon fiber cloth pasted on the bottom surface according to the quadratic trend function are proposed. Research has shown that using CFRP to reinforce reinforced concrete beams on the side can effectively improve the flexural bearing capacity. After comparative analysis, the calculation results of three calculation methods are in good agreement with the experimental values; The correction coefficient η f increases with the increase of the ratio of the bonding height to the beam height ( h f / h ). When the ratio of the bonding height to the beam height ( h f / h ) exceeds 0.25, the value of the correction coefficient η f increases significantly; Especially when the ratio of the pasting height to the beam height ( h f / h ) exceeds 0.5, it is recommended to calculate the flexural bearing capacity of carbon fiber cloth pasted on the bottom surface according to the proposed quadratic trend function for η f ; At the same time, it is recommended to consider the reduction of the cross-sectional area of carbon fiber cloth as compensation when determining the flexural bearing capacity of reinforced concrete beams with carbon fiber cloth pasted on the side according to the calculation of the beam bottom. In order to reduce errors, the utilization coefficient of ψ f is no longer limited. Theoretical analysis shows that there are critical values for the bonding height and thickness of carbon fiber cloth used for reinforcement. When these exceed the critical value, the effect on enhancing load-bearing capacity becomes insignificant or even declines.